Utilization Of Wordwall as An Application for Elementary School Thematic Learning Evaluation - Nisa, Ani Khoiratun; Noptario, Noptario; Muzaini, M. Choirul (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2024)
This research is motivated by the problem of boredom and lack of student motivation in participating in learning evaluations that tend to be monotonous in elementary schools. This study aims to reveal the benefits of using Wordwall as an interactive thematic learning evaluation tool. This study uses a qualitative method with a descriptive approach, where data is obtained through interviews with fifth-grade teachers at an elementary school in Bandar Lampung. The study results indicate that using Wordwall increases student engagement and enthusiasm in participating in the evaluation. In addition, Wordwall allows teachers to create more creative and varied assessments and provide direct feedback to students. Although several obstacles exist, such as the need for an internet connection and paid features, Wordwall has proven effective in increasing student learning motivation. Further research is recommended to explore the use of Wordwall at various levels of education and subjects and discuss the development of Wordwall features to be more flexible and easily accessible without technological limitations. This study's contribution is to show that using Wordwall can increase student engagement and enthusiasm in the evaluation process. Wordwall allows teachers to design more creative and varied assessments and provide direct feedback to students. Although there are some obstacles, such as the need for an internet connection and paid features, Wordwall has proven effective in increasing student learning motivation.